2021
DOI: 10.3390/electronics10030265
|View full text |Cite
|
Sign up to set email alerts
|

Sensorless Control of Bearingless Permanent Magnet Synchronous Motor Based on LS-SVM Inverse System

Abstract: In order to solve the problems of low integration, low reliability, and high cost caused by mechanical sensors used in bearingless permanent magnet synchronous motor (BPMSM) control systems, a novel speed and displacement sensorless control method using a least-squares support vector machine (LS-SVM) left inverse system is proposed in this paper. Firstly, the suspension force generation principle of the BPMSM is introduced, and the mathematical model of the BPMSM is derived. Secondly, the observation principle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The electromechanical sensors utilized inside the bearingless permanent magnet synchronous motor (BPMSM) in [42] have some drawbacks, such as growing the size, expense, and difficulty of the motors, and the detecting outcomes are easily influenced by environmental conditions. A motion and elevation sensorless control solution based on least square support vector machine (LS-SVM) left inversion system is suggested in [42] to address these issues. The reliability and efficacy of the LS-SVM left inversion system experimental method suggested in this study are demonstrated by the realization of the detection of rotational speeds and rotor radial displacement.…”
Section: Future Trends Challenges and Opportunitiesmentioning
confidence: 99%
“…The electromechanical sensors utilized inside the bearingless permanent magnet synchronous motor (BPMSM) in [42] have some drawbacks, such as growing the size, expense, and difficulty of the motors, and the detecting outcomes are easily influenced by environmental conditions. A motion and elevation sensorless control solution based on least square support vector machine (LS-SVM) left inversion system is suggested in [42] to address these issues. The reliability and efficacy of the LS-SVM left inversion system experimental method suggested in this study are demonstrated by the realization of the detection of rotational speeds and rotor radial displacement.…”
Section: Future Trends Challenges and Opportunitiesmentioning
confidence: 99%
“…For an ideal machine that has identical phase windings, the three-phase voltage equation ( 11) contains 9 unknown inductances and 18 unknown elements in the abc Hessian, Γ abc , defined in (9), that are all functions of the rotor position.…”
Section: The Voltage Equation At a Standstillmentioning
confidence: 99%
“…The next step for building the machine model was the Park transformation of the idealized Hessian matrix and the measured data. We developed and used (69) to compute the Park or dq0 transform of the flattened 9×3 Hessian matrix defined by (9). T (ϑ) stands for the Park transformation matrix (47).…”
Section: Park Transformation Of the Hessian Matrixmentioning
confidence: 99%
“…The operation of a traditional PMSM drive requires a shaft-mounted optical encoder or a resolver to determine the rotor position. However, in many industrial installations, the application of the shaft sensor increases the cost and size of the motor, reduces the reliability and the overall ruggedness of the drive, and limits the application in harsh environments [5,7,8]. Furthermore, many shaft sensors provide the initial rotor position with an inadequate resolution and incremental encoders do not provide it at all.…”
Section: Introductionmentioning
confidence: 99%